ISLAMISASI NUSANTARA PERSPEKTIF NASKAH SEJARAH MELAYU - . Azis (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
This article examines of one aspect of islamic historical study inNusantara, they are historical actor, process, time islamization. However, this research utilizes historical sources that have not been widely used to study the issue of literary manuscript history of Malay history.The results of this study generally reinforce one of the “theory” that has been there all along that Islam has come since the end of the seventh century, especially in the early days of the development of Islam in Arabia, involving of scholars actors, royal elite, and traders significantly, and through the top-down although the roles played of booton-up traders and Sufis also can not be ignored at the earlier times.Keywords: Islam, history, nusantara